Letter from Barbara Aronstein Black, Dean of the Faculty of Law, Columbia University - Black, Barbara Aronstein (Columbia Journal of Asian Law, 1987)
Letter from Barbara Aronstein Black, Dean of the Faculty of Law, Columbia University